2010
DOI: 10.3748/wjg.v16.i28.3561
|View full text |Cite
|
Sign up to set email alerts
|

Primary site resection is superior for incurable metastatic colorectal cancer

Abstract: The results indicate that there are benefits from primary site resection for incurable metastatic colorectal cancer with systemic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Our key finding of the association of PTR with improved OS, regardless of chemotherapy administration, is interesting. This result is in consistent with other retrospective studies and meta‐analyses that have shown a survival benefit of PTR. In our cohort the decision for elective palliative PTR was based on multidisciplinary tumor board discussions.…”
Section: Discussionsupporting
confidence: 93%
“…Our key finding of the association of PTR with improved OS, regardless of chemotherapy administration, is interesting. This result is in consistent with other retrospective studies and meta‐analyses that have shown a survival benefit of PTR. In our cohort the decision for elective palliative PTR was based on multidisciplinary tumor board discussions.…”
Section: Discussionsupporting
confidence: 93%
“…Of twenty-three full-text articles that were excluded, twelve had no comparator nonsurgical group [27][28][29][30][31][32][33][34][35][36][37][38] ; four used a non-resection group (that is, ostomy procedures) as comparators [39][40][41][42] ; and another four used patients who underwent curative surgery as the comparator group [43][44][45][46] . Two studies, each with four comparator groups, provided minimal information about those groups, and one had a patient population that overlapped with the population of another study included in the present review 14,47 .…”
Section: Study Selectionmentioning
confidence: 99%
“…A primary resection does ensure that the primary cancer is removed, preventing perforation and stenosis and improving the likelihood of survival, as we also found in the present study. Although a previous study showed that primary site resection has benefits for incurable metastatic CRC [19], the results of prospective randomized studies are awaited, such as the JCOG1007 trial comparing resection of the primary tumor plus chemotherapy with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%